Peluang Pasar Usaha Kecil Melalui Pengadaan Barang Dan Jasa Pemerintah Daerah - Rahmad Purwanto Widiyastomo; Endang Swastuti (Universitas 17 Agustus 1945, 2023)
This article is intended so that small businesses after the national economic recovery period (PEN) can develop pride in the products of micro and small enterprises and cooperatives nationally. Business actors need to take advantage of opportunities to participate in the procurement of local government goods and services through the procurement of goods and services at regional apparatuses through the following types of procurement: (1) defense of procurement; (2) direct electronic procurement and electronic catalogs (e-catalogs) by opening district/city electronic goods and services procurement service units (LPSE) to obtain information openly. In an effort to increase broad market opportunities in the procurement of goods and services, of course micro/small business actors are equipped with: (1) business legality; (2) can establish partnerships; (3) utilizing information technology for promotion; (4) understand the electronic catalog so that they understand about district/city procurement service units (ULP), which are generally in the General Section of the Regional Secretariat.